Developing patient-centric specifications for autologous chimeric antigen receptor T cell therapies. (December 2021) - Zhang, Taylor; Larson, Ryan; Dave, Kedar; Polson, Nolan; Zhang, Heidi
Abstract: With an increasing number of clinical developments and commercial launches of autologous chimeric antigen receptor T-cell therapies, appropriate specification strategies throughout the development lifecycle are critical to ensuring product safety, quality, and patient access on commercialization. A unique aspect of autologous chimeric antigen receptor T-cell therapies is the individualized nature of this class of drug. The heterogeneity in patient leukapheresis material and its impact on drug product quality must be considered in developing a risk-based product specification. This review describes a framework for establishing a patient-centric specification based on correlative analysis linking product attributes with clinical outcomes, variance component analysis deciphering the sources of variability, and appropriate statistical analysis of clinical lot release data.